KHILAFIYAH DALAM IBADAH PADA MASYARAKAT GUNUANG OMEH KABUPATEN LIMA PULUH KOTA - Vito Dasrianto; Hamda Sulfinadia (Jurnal AL-AHKAM, 2020)
Khilafiyah that occurred in Gunuang Omeh because people worshiped to maintain what had  been  practiced  and  left  behind  by  previous  parents  or  scholars.  A review of  the  results  of this study shows that in general, people worship. First, people who are thick with their stance or  understanding,  while  still  practicing  what  they  have  learned  from  previous  scholars, teachers  and  parents.  Second,  people  who  cannot  accept  differences  in  worship  so  that  they establish a place of worship to worship according to the practice they believe is carried out by the elderly who are still on their stance that their practice is the most correct or in worshiping an opinion they believe in. the truth is and the people who worship are willing to accept openly the acts of worship of others who are not the same as their practice of the younger generation. Third,  khilafiyyah  in  Gunuang  Omeh  District  is  not  a  new  thing,  this  is  commonplace  but  the scholars  try  to  unite  and  provide  an  explanation  of  khilafiyah  in  worshiping  the  community even  though  there  are  still  scholars  who  remain  strong  with  their  daily  practices  or  imitate what  has  been  passed on  by their  predecessors.  Fourth,  trying not  to  question the problem of khilâfiyah  and  not  showing  khilâfiyah  in  the  community  even  though  this  kind  of  thinking  is difficult  to  put together  in  the  same  concept  among  Niniak  Mamak  in  Gunang  Omeh  District. Because  this  Niniak  Mamak  has  a  clan  or  leader  of  their  people  who  they  have  to  unite  and provide an explanation for worshiping which they have disputed so far, but in practice Niniak Mamak is also involved in the khilafiyah sphere even though the majority of Niniak Mamak are ulama and community leaders who heard and became a role model by the people in Gunuang Omeh. Key words: Khilafiyah in Worship and Gunuang omeh society